Translation, cross‐cultural adaptation and validation of the traditional Chinese Food Allergy Quality of Life‐Parental Burden questionnaire into simplified Chinese for use in mainland China - Zeen Li; Tingfan Leung; Lang Tian; Haiyan Liu; Wei He; Siyuan Tang; Qirong Chen; Guiyun Wang (Wiley, 2023)
Abstract Aim The study aimed to translate and adapt the traditional Chinese Food Allergy Quality of Life‐Parental Burden Questionnaire (TC‐FAQL‐PB) into simplified Chinese language and determine the validity and reliability of the translated version. Design A methodologic study design involving instrument translation and psychometric evaluation was used for the present study. Methods The simplified Chinese FAQL‐PB (SC‐FAQL‐PB) was developed following Guillemin's guidelines for cross‐cultural adaptation. A convenience sample of 230 participants was recruited. The psychometric properties were examined using internal consistency, test-retest reliability, item discrimination, content validity and construct validity. Results The values of I‐CVI ranged from 0.83 to 1.00. The CFA model revealed that the study supported the two‐factor model. The questionnaire had good internal consistency with a Cronbach's alpha coefficient of 0.946. The item‐total correlation values ranged from 0.707 to 0.866. Test-retest reliability showed that the intraclass correlation coefficient was 0.926 (95% CI, 0.830-0.968).